2022
DOI: 10.1111/1462-2920.16212
|View full text |Cite
|
Sign up to set email alerts
|

The very long‐chain fatty acid elongase FgElo2 governs tebuconazole sensitivity and virulence in Fusarium graminearum

Abstract: Very long‐chain fatty acids (VLCFAs), the precursors for the synthesis of sphingolipids (SLs), play pivotal roles in the development and stress response in eukaryotes. In Saccharomyces cerevisiae, VLCFAs are synthesized in the endoplasmic reticulum (ER) through a four‐step elongation cycle. However, the functions of VLCFA elongases in phytopathogenic fungi remain largely unexplored. Here, we identified a single copy of the VLCFA elongase gene FgELO2 in Fusarium graminearum that causes Fusarium head blight worl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…The synthesis of fatty acids is important for vegetative growth and for the response to stress in eukaryotes. In Fg , deletion mutation of the ergosterol pathway gene (elongase gene; Fg ELO2 ) decreased fungi sensitivity to tebuconazole and also reduced virulence [ 40 ]. In the case of chitosan-treated Fg , we observed a strong up-regulation of genes connected directly with response to oxidative stress such as: catalase 1 (FGSG_06554), catalase 3 (FGSG_06733), catalase 4 (FGSG_12369) up-regulated, respectively, 6.32, 4.02 and 2.18 fold [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of fatty acids is important for vegetative growth and for the response to stress in eukaryotes. In Fg , deletion mutation of the ergosterol pathway gene (elongase gene; Fg ELO2 ) decreased fungi sensitivity to tebuconazole and also reduced virulence [ 40 ]. In the case of chitosan-treated Fg , we observed a strong up-regulation of genes connected directly with response to oxidative stress such as: catalase 1 (FGSG_06554), catalase 3 (FGSG_06733), catalase 4 (FGSG_12369) up-regulated, respectively, 6.32, 4.02 and 2.18 fold [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the up-regulated expression of FGSG_0007 was consistent with the qPCR data, and the results confirmed the RNA-Seq approach to quantify the expression. Previously, several articles have used qPCR as an alternative to gene expression data to verify the authenticity of results [ 27 , 40 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our study identified VLCFA biosynthesis as another metabolic pathway crucial for host infection by M. oryzae . Due to the conservation of enzymes involved in VLCFA biosynthesis, it is very likely that this metabolic pathway is broadly important for pathogenesis of many other fungal pathogens such as F. graminearum (Wang, Chen, et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In plants, VLCFAs are imperative to programmed cell death during the abiotic stress response, cell elongation of cotton fibres, cell plate formation, cell proliferation in shoot apex and regeneration of callus (Bach et al., 2011 ; Du Granrut & Cacas, 2016 ; Haslam & Kunst, 2013 ; Liu et al., 2024 ; Luzarowska et al., 2023 ; Shang et al., 2016 ; Yang et al., 2023 ; Zheng et al., 2005 ). Increasing evidence has demonstrated the importance of VLCFAs for host infection by pathogens including M. oryzae (He et al., 2020 ), Fusarium graminearum (Wang, Chen, et al., 2022 ), protozoan parasite Toxoplasma gondii (Ramakrishnan et al., 2015 ) and human cytomegalovirus (Koyuncu et al., 2013 ). However, the biosynthesis and mechanistic role of VLCFAs remains poorly understood in microbial pathogens.…”
Section: Introductionmentioning
confidence: 99%